Penerapan Fuzzy Tsukamoto pada Alat Deteksi Penyakit Hipoksemia, Hipotermia, Hipertensi, dan Diabetes untuk Health Care Kiosk - Heny Yuniarti; Riyanto Sigit; Muhammad Aunur Rofiq (Politeknik Negeri Batam, 2020)
Most of people in Indonesia need fast, right, and accurate health medical service. But as we know in hospital takes many time just for check our health condition. This research make a Health Care Kiosk for medical check up, without using a doctor, so that kiosk can detect many deseases automatically. This research focused on 4 deseases such as hypothermia, hypoxemia, hypertension and diabetes. System using Embedded PC for data processing automatically. There are many medical sensor such as thermometer, heart rate sensor, blood pressure sensor, SPO2 sensor, and glucometer sensor for check health condition. System can make a decision if that patient healthy or not automatically because it uses fuzzy method for that decision. The result of this paper is this system can detect every deseases and that error for each sensor are body temperature has 1.05% error, oxygen level has 1.90% error, heart rate has 5.78% error, blood pressure sistolic has 4.16% error, blood pressure diastolic has 4.87% error and glucosa level in blood has 4.01% error. This system integrated with database MySQL for save that result. The accuracy from fuzzy method is 100% right and fuzzy tsukamoto can process input well.